Nutrient Composition, Antioxidant Activities and Anti-Inflammatory Effect of Jujube Fruit: A General Review - Sabri, Suha M.; Takruri, Hamed R.; Al Ismail, Khalid M. (Journal of Pharmacy and Nutrition Sciences, 2021)
Jujube (Ziziphus jujuba) fruit belongs to the Rhamnaceous family and is widely located in the tropical and subtropical regions of Asia as well as in the Mediterranean regions including Jordan. Therefore, the aim of this review was to illustrate the nutritional value of jujube fruit and its importance in human health protection as antioxidant and anti-inflammatory agent. Recently, several scientific reports have been carried out about the presence of many biologically active compounds from Z. jujuba, which may have high potential benefit in human nutrition, health, and disease. Based on previous studies, jujube fruit can possess good antioxidant and anti-inflammatory activity rendering it a functional food. Since jujube fruit has diverse biological activity, further biological studies including clinical-based studies are recommended to explore the health promoting effect of jujube.